2023
DOI: 10.3892/ol.2023.13922
|View full text |Cite
|
Sign up to set email alerts
|

Role of RNA methylation in the regulation of pancreatic cancer stem cells (Review)

Abstract: Pancreatic cancer stem cells (CSCs) play a key role in the initiation and progression of pancreatic adenocarcinoma (PDAC). CSCs are responsible for resistance to chemotherapy and radiation, and for cancer metastasis. Recent studies have indicated that RNA methylation, a type of RNA modification, predominantly occurring as m6A methylation, plays an important role in controlling the stemness of cancer cells, therapeutic resistance against chemotherapy and radiation therapy, and their overall relevance to a patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“… 9 MeRIP‐seq has been performed on various cancer cell tumors, and m6A has been found to be associated with malignant transformation of cancer. 10 It has been reported that inhibition of expression of METTL14 (m6A methyltransferase) and ALKBH5 (demethylase) in human breast cancer cell lines inhibits cancer growth and invasion. 11 The 3′ UTR of homeobox containing 1 (HMBOX1) mRNA is modified with m6A by METTL3, and its translation is repressed in prostate cancer cell LNCaP compared with epithelial cell RWPE‐1, a normal cell line, and telomere length and p53 signaling are aberrant.…”
Section: Introductionmentioning
confidence: 99%
“… 9 MeRIP‐seq has been performed on various cancer cell tumors, and m6A has been found to be associated with malignant transformation of cancer. 10 It has been reported that inhibition of expression of METTL14 (m6A methyltransferase) and ALKBH5 (demethylase) in human breast cancer cell lines inhibits cancer growth and invasion. 11 The 3′ UTR of homeobox containing 1 (HMBOX1) mRNA is modified with m6A by METTL3, and its translation is repressed in prostate cancer cell LNCaP compared with epithelial cell RWPE‐1, a normal cell line, and telomere length and p53 signaling are aberrant.…”
Section: Introductionmentioning
confidence: 99%